The Impact of Hydration and Temperature on Bacterial Diversity in Arid Soil Mesocosms - Št'ovíček, Adam; Azatyan, Ani; Soares, M. Ines M.; Gillor, Osnat (Frontiers in Microbiology, 2017)
Hot desert ecosystems experience rare and unpredictable rainfall events that resuscitate the arid flora and fauna. However, the effect of this sudden abundance of water on soil microbial communities is still under debate. We modeled varying rainfall amounts and temperatures in desert soil mesocosms and monitored the microbial community response over a period of 21 days. We studied two different wetting events, simulating heavy (50 mm) and light (10 mm) rain, as well as three different temperature regimes: constant 25° or 36°C, or a temperature diurnal cycle alternating between 36 and 10 °C. Amplicon sequencing of the bacterial ribosomal RNA revealed that rain intensity affects the soil bacterial community, but the effects are mitigated by temperature. The combination of water-pulse intensity with lower temperature had the greatest effect on the bacterial community. These experiments demonstrated that the soil microbial response to rain events is dependent not only on the intensity of the water pulse but also on the ambient temperature, thus emphasizing the complexity of bacterial responses to highly unpredictable environments.